2010
DOI: 10.1021/om100385m
|View full text |Cite
|
Sign up to set email alerts
|

C−H Bond Activation of Arenes by [8,8′-μ-I-3,3′-Co(1,2-C2B9H10)2] in the Presence of Sterically Hindered Lewis Bases

Abstract: Reactions of the iodonium derivative of cobalt bis(dicarbollide) anion [μ-8,8′-I-3,3′-Co(1,2-C2B9H10)2] with Lewis bases in aromatic solvents were studied. The reactions proceed through the iodonium bridge opening, and the structure of the reaction products depends strongly on the nature of the Lewis base and solvent used. The reactions with conventional Lewis bases (L) give the corresponding products of Lewis base addition, [8-L-8′-I-3,3′-Co(1,2-C2B9H10)2], whereas the reactions with sterically hindered Lewis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 33 publications
(32 reference statements)
1
24
0
Order By: Relevance
“…14, left) À anion is also feasible, and this can be viewed as a masked form of a borinium cation. A related "quasi-borinium" cation, 22, derived from [μ- 8,8 0 -I-3,3 0 -Co(1,2-C 2 B 9 H 10 ) 2 ] has been proposed by Sivaev and co-workers to be the active electrophile in the dehydroboration of arenes [67,68]. Other carborane compounds with "naked boron vertices" have been used by Michl et al to effect the borodesilation of arylsilanes [69].…”
Section: Intermolecular Electrophilic Aromatic Borylationmentioning
confidence: 99%
“…14, left) À anion is also feasible, and this can be viewed as a masked form of a borinium cation. A related "quasi-borinium" cation, 22, derived from [μ- 8,8 0 -I-3,3 0 -Co(1,2-C 2 B 9 H 10 ) 2 ] has been proposed by Sivaev and co-workers to be the active electrophile in the dehydroboration of arenes [67,68]. Other carborane compounds with "naked boron vertices" have been used by Michl et al to effect the borodesilation of arylsilanes [69].…”
Section: Intermolecular Electrophilic Aromatic Borylationmentioning
confidence: 99%
“…Recently we found that reaction of the iodonium derivative of cobalt bis(dicarbollide) [m-8,8 0 -I-3,3 0 -Co(1,2-C 2 B 9 H 10 ) 2 ] (1) with benzene in the presence of sterically hindered Lewis bases results in the benzene CeH activation with formation of the corresponding phenyl derivative [12]. It was assumed that the reaction proceeds through breakage of the iodonium bridge with formation frustrated Lewis pair [14] between boron-centered quasi-borinium cation (Lewis acid) and sterically hindered Lewis base.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of activated arenes (containing electron-donating groups) such as toluene, the reaction proceeds even in the absence of Lewis base. At the same time, CeH activation of sterically hindered electron rich arenes, such as mesitylene, needs the presence of sterically hindered Lewis base [12].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations